Modeling the spread of Covid-19 pandemic in Morocco - Zine, Houssine (2021)
Nowadays, coronavirus disease 2019 (Covid-19) poses a great threat to public health and economy worldwide. Unfortunately, there is yet no effective drug for this disease. For this, several countries have adopted multiple preventive interventions to avoid the spread of Covid-19. Here, we propose a delayed mathematical model to predict the epidemiological trend of Covid-19 in Morocco. Parameter estimation and sensitivity analysis of the proposed model are rigorously studied. Moreover, numerical simulations are presented in order to test the effectiveness of the preventive measures and strategies that were imposed by the Moroccan authorities and also help policy makers and public health administration to develop such strategies.